Statistical analysis with R essentials - Schmuller, Joseph (John Wiley & Sons, Inc., 2024)
Statistical Analysis with R Essentials For Dummies is your reference to all the core concepts about R-the widely used, open-source programming language and data analysis tool. This no-nonsense book gets right to the point, eliminating review material, wordy explanations, and fluff. Understand all you need to know about the foundations of R, swiftly and clearly. Perfect for a brush-up on the basics or as an everyday desk reference on the job, this is the reliable little book you can always turn to for answers. This book is to the point, focusing on the key topics readers need to know about this popular programming language. Great for supplementing classroom learning, reviewing for a certification, or staying knowledgeable on the job.
Includes index. - Description based on print version record
Keywords: Mathematical statistics -- Data processing; Statistics -- Data processing; R (Computer program language); Statistique mathématique; Informatique; Statistique; Informatique; R (Langage de programmation)